hydroxycinnamoyltransferase responsible for synthesizing suberin aromatics in Arabidopsis - Gou, Jin-Ying; Yu, Xiao-Hong; Liu, Chang-Jun (Proceedings of the National Academy of Sciences - PNAS, 2009)
Suberin, a polyester polymer in the cell wall of terrestrial plants, controls the transport of water and nutrients and protects plant from pathogenic infections and environmental stresses. Structurally, suberin consists of aliphatic and aromatic domains; p-hydroxycinnamates, such as ferulate, p-coumarate, and/or sinapate, are the major phenolic constituents of the latter. By analyzing the "wall-bound" phenolics of mutant lines of Arabidopsis deficient in a family of acyl-CoA dependent acyltransferase (BAHD) genes, we discovered that the formation of aromatic suberin in Arabidopsis, primarily in seed and root tissues, depends on a member of the BAHD superfamily of enzymes encoded by At5g41040. This enzyme exhibits an ω-hydroxyacid hydroxycinnamoyltransferase activity with an in vitro kinetic preference for feruloyl-CoA and 16-hydroxypalmitic acid. Knocking down or knocking out the At5g41040 gene in Arabidopsis reduces specifically the quantity of ferulate in suberin, but does not affect the accumulation of p-coumarate or sinapate. The loss of the suberin phenolic differentially affects the aliphatic monomer loads and alters the permeability and sensitivity of seeds and roots to salt stress. This highlights the importance of suberin aromatics in the polymer's function.